The king of infinite space - Faye, Lyndsay (G.P. Putnam's Sons, 2021)
"In this lush, magical, queer, and feminist take on Hamlet in modern-day New York City, a neuro-atypical philosopher, along with his best friend Horatio and artist ex-fiancé Lia, are caught up in the otherworldly events surrounding the death of his father"--